Unrecognized grief - Prevalence and comorbidity of prolonged grief among refugees in Sweden - Anna Leiler; Jennifer Meurling; Elisabet Rondung; Shervin Shahnavaz; Gerhard Andersson; Anna Bjärtå (Elsevier, 2024)
Refugees often experience multiple losses. Despite this, and even though the loss is often due to unnatural causes and violent killings, the presence of Prolonged Grief (PG) among refugees may be obscured by other diagnoses such as depression and post-traumatic stress disorder (PTSD). In this cross-sectional study, we assessed the prevalence of PG and its comorbidity with depression and PTSD among 679 adult refugees in Sweden. Results showed that 401 (59.06 %) individuals had lost someone close to them, whom they were grieving intensely. Of these, 76 individuals (18.95 % of 401) fulfilled the criteria for PG. In the full sample, 304 individuals fulfilled the criteria for depression and 56 (18.42 % of 304) of these individuals also fulfilled the criteria for PG. Similarly, 315 fulfilled the criteria for PTSD. Among these individuals, 201 reported loss and 64 (20.32 % of 315) also fulfilled the criteria for PG. The results indicate that behind symptoms of depression and PTSD, there may be a layer of grief. This needs to be considered if we are to provide accurate and effective assessments and interventions for refugees.